2018
DOI: 10.1016/j.cub.2018.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Purging of Strongly Deleterious Mutations Explains Long-Term Persistence and Absence of Inbreeding Depression in Island Foxes

Abstract: Summary The recovery and persistence of rare and endangered species are often threatened by genetic factors, such as the accumulation of deleterious mutations, loss of adaptive potential, and inbreeding depression [1]. Island foxes (Urocyon littoralis), the dwarfed descendants of mainland gray foxes (U. cinereoargenteus), have inhabited California’s Channel Islands for >9,000 years [2-4]. Previous genomic analyses revealed island foxes have exceptionally low levels of diversity and elevated levels of putativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
210
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(250 citation statements)
references
References 46 publications
17
210
4
Order By: Relevance
“…Overall, these results are consistent with recent empirical findings in which small populations or populations at the expansion front carry more homozygous derived deleterious mutations [26,27,86]. These deleterious mutations in homozygous state are expected to be purged by purifying selection [23,92]. Populations from Cascadia, with higher effective population sizes, contain a higher number of putatively deleterious variants in heterozygous state, as expected from population genetics theory.…”
Section: Accumulation Of Deleterious Mutations Under Complex Demographysupporting
confidence: 90%
“…Overall, these results are consistent with recent empirical findings in which small populations or populations at the expansion front carry more homozygous derived deleterious mutations [26,27,86]. These deleterious mutations in homozygous state are expected to be purged by purifying selection [23,92]. Populations from Cascadia, with higher effective population sizes, contain a higher number of putatively deleterious variants in heterozygous state, as expected from population genetics theory.…”
Section: Accumulation Of Deleterious Mutations Under Complex Demographysupporting
confidence: 90%
“…For example, clonal variants tend to accrue recessive deleterious variants over time, because these variants are under recessive selection and permanently held in a heterozygous state (37). Similarly, forward simulations have shown that moderately and weakly deleterious variants accumulate under various demographic regimes (84). Here we have shown that the SV burden is elevated by 25% to 35% in our japonica and indica samples relative to rufipogon (Fig.…”
Section: Svs and Domesticationsupporting
confidence: 54%
“…A major gap in our understanding is how reduced selection efficacy and purging jointly determine the mutation load in wild populations. Theoretical predictions are well established 13,15,18,20 but empirical evidence is conflicting 9,21,22 including for humans (see e.g. 2331 .…”
Section: Main Textmentioning
confidence: 99%
“…2331 . Previous research used changes in fitness to infer possible purging events, 7,20,3234 , but changes in fitness can result from causes unrelated to purging 12,35 . Direct evidence for purging exists only for isolated mountain gorilla populations that split off larger lowland populations ~20’000 years ago 36 .…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation